The time course of figure-ground reversal. - Hulleman, J; Gedamke, L; Humphreys, G (2005)
We report the results from five experiments employing a modified version of the short-term visual matching (STVM) method introduced by Driver and Baylis (1996). In STVM, participants see a study display with ambiguous figure-ground relations. After the study display, participants have to decide which of two shapes in a match display was seen before in the study display. STVM has been used by Vecera, Vogel, and Woodman (2002) to demonstrate that the lower region is a figure-ground cue. In our modified version of STVM, the study stimulus was preceded by a brief prime. This caused a biasing of the figural interpretation of the ambiguous figure-ground displays that contained the lower region cue. We show that 100-msec priming with an unambiguous display is enough to affect the subsequent interpretation of the ambiguous figure-ground display. It takes maximally 350 msec to complete a transition from the nondominant interpretation to the dominant interpretation of an ambiguous figure-ground display that contains the lower region cue.